Adrenal venous sampling in a patient with left inferior vena cava. Issue 4 (2nd March 2017) - Fujii, Yuichi; Ueda, Tomohiro; Uchimura, Yuko; Teragawa, Hiroki
Key Clinical Message: Adrenal venous sampling (AVS), although difficult, is recommended for patients with primary aldosteronism (PA) to diagnose the subtype. Recognizing anatomical variation is key to a successful AVS. We report on a patient with PA and left inferior vena cava (IVC) whose left adrenal vein drained directly into the IVC. Abstract : Adrenal venous sampling (AVS), although difficult, is recommended for patients with primary aldosteronism (PA) to diagnose the subtype. Recognizing anatomical variation is key to a successful AVS. We report on a patient with PA and left inferior vena cava (IVC) whose left adrenal vein drained directly into the IVC.